Correlation of the A-FABP Gene Polymorphism and mRNA Expression with Intramuscular Fat Content in Three-Yellow Chicken and Hetian-Black Chicken. Issue 1 (2nd January 2017) - Wang, Yong; Chen, Hongwei; Han, Diangang; Chen, Ying; Muhatai, Gemingguli; Kurban, Tursunjan; Xing, Jinming; He, Jianzhong
ABSTRACT: The adipocyte-type fatty acid-binding protein (A-FABP) is considered a candidate gene for fat metabolism; thus, it affects fat deposition in chickens. The present study was designed to examine the polymorphism and mRNA abundance of the A-FABP gene with intramuscular fat (IMF) in the pectoralis muscles (PM) and leg muscles (LM) of Three-yellow Chicken (TYC) and Hetian-black Chicken (HTBC). In total, 60 TYCs and 60 HTBCs were sacrificed using exsanguination at market age. The IMF contents of the PM and LM in the HTBC were significantly higher than those in the TYC. Three genotypes of the A-FABP gene first exon, AA, AB, and BB, were examined by polymerase chain reaction-single strand conformation polymorphism (PCR-SSCP), and a C51 T mutational site, which is a silent substitution mutation, was revealed. The IMF contents of the AA genotype in the PM of the HTBC were significantly higher than those in the AB genotype; thus, the C51 T mutable site is a gene marker for selecting a higher IMF content in the PM of the HTBC. The relative expression of the A-FABP mRNA in the LM of the HTBC, which was measured by quantitative real-time PCR, was significantly higher than in the TYC. A significantly positive association was detected between A-FABP expression with the IMF contents of the PM and LM of both the TYC and the HTBC. These results provide basic data that might be helpful to further research the role of the A-FABP gene in fat deposition and fatty acid metabolism in chickens.